Pengembangan Ekonomi Masyarakat di Kampung Olahan Singkong, Wonosari, Ngaliyan, Semarang - Agus Riyadi (UIN Siber Syekh Nurjati Cirebon, 2021)
This study aims to determine how the process and the results of community economic development in The Cassava Processing Village, Wonosari Village, Ngaliyan District, Semarang City. This type of research is descriptive qualitative. Data collection techniques through observation, interviews and documentation. The results of this study indicate that: 1) The process of developing the community's economy in the cassava processing village includes: (1) Training on processing cassava according to hygienic standards and (2) Evaluation of the process of training activities. 2) The results of community economic development based on local potential in Processed Cassava Village include: (1) Community/group members increase in the economy, (2) The increasing independence of the group, (3) Increasing concern for the environment, (4) Increasing quality of human resources.